Saponin content in medicinal plants in response to application of organic and inorganic fertilizers: a meta-analysis - Lv, Junyan; Liu, Shouzan; Hu, Chunli; Ding, Lan; Wang, Hongzhen; Li, Xin; Yang, Feng; Shen, Qiong; Zhang, Hongbin; Ma, Guobiao; Zhang, Shaobo; Bai, Yan (Frontiers in Plant Science, 2025)
The application of fertilizers is a key agronomic practice in the artificial cultivation of medicinal plants, aiming to boost yields and enhance the levels of their bioactive constituents. However, systematic investigations on the influence of various fertilizers on the concentration of active compounds in saponin-containing medicinal plants remain insufficient. In this study, 966 experimental outcomes from 29 papers were analyzed via meta-analysis to examine the effects of organic fertilizers, inorganic fertilizers, and their combined application on the levels of different saponin monomers in medicinal plants. The findings from the meta-analysis revealed that inorganic fertilizers contribute positively to the accumulation of saponins such as Rg1 in ginseng, Rb1, Rc, Rd, Re, and Rg1, in addition to the saponins from Paris polyphylla, Dioscorea, Panax quinquefolius, and Platycodon grandiflorus. Moreover, the application of organic fertilizers was found to markedly elevate the concentrations of Notoginsenoside R1, Ginsenoside Rb1, Ginsenoside Rb2, Re, and Rg1, along with Lancemasid saponins and Quinoa saponins. The combined use of both organic and inorganic fertilizers was shown to effectively increase the levels of Notoginsenoside R1 and Panax ginsenosides, encompassing Rb1, Rb2, Rc, Rd, Re, and Rg1. Overall, the results suggest that both individual and combined applications of organic and inorganic fertilizers have a positive impact on the enhancement of saponin monomers in medicinal plants. However, inorganic fertilizers promote the increase of saponin content, their prolonged use may lead to soil compaction and acidification, which could compromise the yield and quality of medicinal plants. On the other hand, organic fertilizers improve the soil environment and stimulate saponin accumulation, they do not supply all the nutrients required for the sustained growth of these plants. Therefore, a balanced fertilization strategy combining both organic and inorganic fertilizers is recommended as the optimal approach for cultivating saponin-rich medicinal plants.